2015
DOI: 10.1007/s40710-015-0082-6
|View full text |Cite
|
Sign up to set email alerts
|

Multi-method Modeling Framework for Support of Integrated Water Resources Management

Abstract: The existing definition of integrated water resources management (IWRM) promotes a holistic approach to water resources management practice. The IWRM deals with planning, design and operation of complex systems in order to control the quantity, quality, temporal and spatial distribution of water with the main objective of meeting human and ecological needs and providing protection from water disasters. One of the main challenges of IWRM is development of tools for operational implementation of the concept and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 36 publications
(38 reference statements)
0
16
0
Order By: Relevance
“…The components of the conceptual framework for this study transmit the requisite information to other participants directly as shown in Figure 2. According to the IWRM concept and to promote the theory of system view, this model will provide an authentic representation of the interactions between the physical environment and implementation of IWRM strategies (Nikolic & Milicevic 2012;Nikolic & Simonovic, 2015). The modeling paradigm encourages model scenarios to analyze different issues of "what-if" management (Nikolic & Simonovic, 2015).…”
Section: The Study Conceptual Frameworkmentioning
confidence: 99%
“…The components of the conceptual framework for this study transmit the requisite information to other participants directly as shown in Figure 2. According to the IWRM concept and to promote the theory of system view, this model will provide an authentic representation of the interactions between the physical environment and implementation of IWRM strategies (Nikolic & Milicevic 2012;Nikolic & Simonovic, 2015). The modeling paradigm encourages model scenarios to analyze different issues of "what-if" management (Nikolic & Simonovic, 2015).…”
Section: The Study Conceptual Frameworkmentioning
confidence: 99%
“…Ticehurst et al, 2007), as well as different couplings of multiple methods (e.g. Nikolic and Simonovic 2015).…”
Section: Overcoming Data Limitationsmentioning
confidence: 99%
“…Typhoons with heavy rainfall and strong wind often cause severe floods and disasters. Providing protection from flood‐related disasters is essential for the typhoon‐prone areas, which is also one of the objectives in integrated water resources management (Fedra, ; Nikolic and Simonovic, ). Owing to the huge negative social impacts of typhoons, accurate typhoon forecasting is a priority of the operational weather forecast centres in the western North Pacific, especially in Taiwan (Hsiao et al , ).…”
Section: Introductionmentioning
confidence: 99%